1992
DOI: 10.1016/1044-0305(92)85031-e
|View full text |Cite
|
Sign up to set email alerts
|

Determination of orders of relative alkali metal ion affinities of crown ethers and acyclic analogs by the kinetic method

Abstract: Ladders of relative alkali ion affinities of crown ethers and acyclic analogs were constructed by using the kinetic method. The adducts consisting of two different ethers bound by an alkali metal ion, (M1 + Cat + M2)(+), were formed by using fast atom bombardment ionization to desorb the crown ethers and alkali metal ions, then collisionally activated to induce dissociation to (M1 + Cat)(+) and (M2 + Cat)(+) ions. Based on the relative abundances of the cationized ethers formed, orders of relative alkali ion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 49 publications
4
52
0
Order By: Relevance
“…The first of these studies (Liou & Brodbelt, 1992b) demonstrated a significant size effect for the binding of alkali ions with crown ethers. For example, Li þ binds significantly more strongly to 15-crown-5 than to any other crown.…”
Section: B Orders Of Alkali Ion Affinities By the Kinetic Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…The first of these studies (Liou & Brodbelt, 1992b) demonstrated a significant size effect for the binding of alkali ions with crown ethers. For example, Li þ binds significantly more strongly to 15-crown-5 than to any other crown.…”
Section: B Orders Of Alkali Ion Affinities By the Kinetic Methodsmentioning
confidence: 96%
“…From the intensities of the ML and ML' fragments, conclusions can be drawn with respect to the relative binding strengths of the two ligands. This approach was applied to the alkali ion heterodimers with two different crown ether ligands attached to the same central ion (Liou & Brodbelt, 1992b) as well as the complexes of one crown ether with a MM' X þ fragment, where M and M' correspond to two different alkali metal ions and X represents a halogen counter ion (Maleknia & Brodbelt, 1992).…”
Section: B Orders Of Alkali Ion Affinities By the Kinetic Methodsmentioning
confidence: 99%
“…Brodbelt and co-workers determined the relative alkali ion affinities of crown ethers and acyclic analogs by using kinetic methods. [17][18][19] Again, crown ethers showed higher affinities for specific sizes of metal ions and the size selectivity was more pronounced for the smaller ions. In addition, computational studies have been reported to address the issues of bond energies or enthalpies, [20][21][22][23][24][25][26][27] criteria of optimal structures, [28][29][30] and energy barriers for metal ion migration from one binding site to the other.…”
Section: Introductionmentioning
confidence: 97%
“…Na + > K + > Cs + . [16][17][18][19] Armentrout's group measured bond dissociation energies (BDEs) of M + (12-crown-4) (M ) Li, Cs), which vary from ∼0.90 eV for Cs + to 3.90 eV for Li + , [20][21][22][23] in good agreement with a theoretical study. 24 Conceptually, dioxanes can be regarded as crown ethers, i.e., 6-crown-2.…”
Section: Introductionmentioning
confidence: 69%